Answer
Verified
501.3k+ views
Hint- Here, we will be using the concept of complex conjugate pairs and the formulas for sum and product of the roots of any quadratic equation.
Given, quadratic equation is ${z^2} + \alpha z + \beta = 0{\text{ }} \to {\text{(1)}}$ where $\alpha ,\beta $ be real and $z$ be a complex number.
It is also given that the two distinct roots of the above quadratic equation lies on the line ${\text{Re}}\left( z \right) = 1$ which means that the real part of both the roots is 1.
As we know that the complex roots corresponding to any quadratic equation occurs in conjugate pairs.
Therefore, let us suppose the two distinct roots of the given quadratic equation be \[{z_1} = 1 + i\left( a \right)\] \[{z_2} = 1 - i\left( a \right)\].
Also we know that for any general quadratic equation $a{z^2} + bz + c = 0{\text{ }} \to {\text{(2)}}$ with two roots as ${z_1}$ and ${z_2}$,
Sum of roots of the quadratic equation, ${z_1} + {z_2} = \dfrac{{ - b}}{a}{\text{ }} \to {\text{(3)}}$
Product of roots of the quadratic equation, ${z_1}{z_2} = \dfrac{c}{a}{\text{ }} \to {\text{(4)}}$
On comparing equation (1) with equation (2), we get
$a = 1,{\text{ }}b = \alpha $ and $c = \beta $
Using equation (3), we get
${z_1} + {z_2} = \dfrac{{ - b}}{a} \Rightarrow 1 + i\left( a \right) + 1 - i\left( a \right) = \dfrac{{ - \alpha }}{1} \Rightarrow 2 = - \alpha \Rightarrow \alpha = - 2$
Using equation (4), we get
\[{z_1}{z_2} = \dfrac{c}{a} \Rightarrow \left[ {1 + i\left( a \right)} \right]\left[ {1 - i\left( a \right)} \right] = \dfrac{\beta }{1} \Rightarrow 1 + i\left( a \right) - i\left( a \right) - {i^2}\left( {{a^2}} \right) = \beta \Rightarrow 1 - {i^2}\left( {{a^2}} \right) = \beta \]
As we know that ${i^2} = - 1$ \[ \Rightarrow 1 - \left( { - 1} \right)\left( {{a^2}} \right) = \beta \Rightarrow \beta = 1 + {a^2}\]
Also we know that ${a^2} \geqslant 0$ (always) $ \Rightarrow 1 + {a^2} \geqslant 1 \Rightarrow \beta \geqslant 1 \Rightarrow \beta \in [1,\infty )$
Hence, option D is correct.
Note- For any general quadratic equation $a{z^2} + bz + c = 0$ where $z$ is a complex number, if one of the root is $d + i\left( e \right)$ then the other root will appear as the complex conjugate of the first root i.e., $d - i\left( e \right)$.
Given, quadratic equation is ${z^2} + \alpha z + \beta = 0{\text{ }} \to {\text{(1)}}$ where $\alpha ,\beta $ be real and $z$ be a complex number.
It is also given that the two distinct roots of the above quadratic equation lies on the line ${\text{Re}}\left( z \right) = 1$ which means that the real part of both the roots is 1.
As we know that the complex roots corresponding to any quadratic equation occurs in conjugate pairs.
Therefore, let us suppose the two distinct roots of the given quadratic equation be \[{z_1} = 1 + i\left( a \right)\] \[{z_2} = 1 - i\left( a \right)\].
Also we know that for any general quadratic equation $a{z^2} + bz + c = 0{\text{ }} \to {\text{(2)}}$ with two roots as ${z_1}$ and ${z_2}$,
Sum of roots of the quadratic equation, ${z_1} + {z_2} = \dfrac{{ - b}}{a}{\text{ }} \to {\text{(3)}}$
Product of roots of the quadratic equation, ${z_1}{z_2} = \dfrac{c}{a}{\text{ }} \to {\text{(4)}}$
On comparing equation (1) with equation (2), we get
$a = 1,{\text{ }}b = \alpha $ and $c = \beta $
Using equation (3), we get
${z_1} + {z_2} = \dfrac{{ - b}}{a} \Rightarrow 1 + i\left( a \right) + 1 - i\left( a \right) = \dfrac{{ - \alpha }}{1} \Rightarrow 2 = - \alpha \Rightarrow \alpha = - 2$
Using equation (4), we get
\[{z_1}{z_2} = \dfrac{c}{a} \Rightarrow \left[ {1 + i\left( a \right)} \right]\left[ {1 - i\left( a \right)} \right] = \dfrac{\beta }{1} \Rightarrow 1 + i\left( a \right) - i\left( a \right) - {i^2}\left( {{a^2}} \right) = \beta \Rightarrow 1 - {i^2}\left( {{a^2}} \right) = \beta \]
As we know that ${i^2} = - 1$ \[ \Rightarrow 1 - \left( { - 1} \right)\left( {{a^2}} \right) = \beta \Rightarrow \beta = 1 + {a^2}\]
Also we know that ${a^2} \geqslant 0$ (always) $ \Rightarrow 1 + {a^2} \geqslant 1 \Rightarrow \beta \geqslant 1 \Rightarrow \beta \in [1,\infty )$
Hence, option D is correct.
Note- For any general quadratic equation $a{z^2} + bz + c = 0$ where $z$ is a complex number, if one of the root is $d + i\left( e \right)$ then the other root will appear as the complex conjugate of the first root i.e., $d - i\left( e \right)$.
Recently Updated Pages
Fill in the blanks with suitable prepositions Break class 10 english CBSE
Fill in the blanks with suitable articles Tribune is class 10 english CBSE
Rearrange the following words and phrases to form a class 10 english CBSE
Select the opposite of the given word Permit aGive class 10 english CBSE
Fill in the blank with the most appropriate option class 10 english CBSE
Some places have oneline notices Which option is a class 10 english CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
When was Karauli Praja Mandal established 11934 21936 class 10 social science CBSE
Which are the Top 10 Largest Countries of the World?
What is the definite integral of zero a constant b class 12 maths CBSE
Why is steel more elastic than rubber class 11 physics CBSE
Distinguish between the following Ferrous and nonferrous class 9 social science CBSE
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE